THE PENGARUH CAPACITY BUILDING TERHADAP KINERJA SKPD PEMERINTAH KOTA MAKASSAR - Sitti Rahmawati Arfah (Jurnal Administrasi Negara, 2018)
Capacity development designed to improve the efficiency, effectiveness and responsiveness of organizational performance. This study aims to determine capacity building for the influence of capacitybuilding on the performacelocal apparaturwork units of the governmentmakassar city. The data were analyzed using questionnaire anddocumentation techniques.They were analyzed using multiple regression with partial and simultaneous hypothesis test. The popula-tion consisted of 53 Local Apparatur Work Units of the Government of Makassar City and 106 respondents of each unitLocal Apparatur Work Units of the Government.The results of the results indicate that there is a positive and significant influence of the development of human resources, the strengtehingof organization and the reform of institution on the performance of organization. This means that the performance of Local Apparatur Work Units of the Government of Makassar City is generally influenced, and the reform of institution. This remains are influenced by other factors which are not under the research model.